The Intriguing Evolutionary Journey of Enteroinvasive E. coli (EIEC) toward Pathogenicity - Pasqua, Martina; Michelacci, Valeria; Di Martino, Maria Letizia; Tozzoli, Rosangela; Grossi, Milena; Colonna, Bianca; Morabito, Stefano; Prosseda, Gianni (Frontiers in Microbiology, 2017)
Among the intestinal pathogenic E. coli, enteroinvasive E. coli (EIEC) are a group of intracellular pathogens able to enter epithelial cells of colon, multiplicate within them and move between adjacent cells with a mechanism similar to Shigella, the ethiological agent of bacillary dysentery. Despite EIEC belong to the same pathotype of Shigella, they neither have the full set of traits that define Shigella nor have undergone the extensive gene decay observed in Shigella. Molecular analysis confirms that EIEC are widely distributed among E. coli phylogenetic groups and correspond to bioserotypes found in a dozen of E. coli serogroups. Like Shigella, also in EIEC the critical event towards a pathogenic life-style consisted in the acquisition by horizontal gene transfer of a large F-type plasmid containing the genes required for invasion, intracellular survival and spreading through the intestinal mucosa. In Shigella, the ample gain in virulence determinants has been counteracted by a substantial loss of functions that, although important for the survival in the environment, are redundant or deleterious for the life inside the host. The pathoadaptation process that has led Shigella to modify its metabolic profile and increase its pathogenic potential, is still in infancy in EIEC, although maintenance of some features typical of E. coli might favour their emerging relevance as intestinal pathogens worldwide, as documented by recent outbreaks in industrialized countries. In this review, we will discuss the evolution of EIEC towards Shigella-like invasive forms going through the epidemiology, including the emergence of new virulent strains, their genome organization and the complex interactions they establish with the host.